Strategi Pemberdayaan Anggota Kelompok Jasema di Kalurahan Terong Kapanewon Dlingo Kabupaten Bantul - Nurul Oktaviani, Oktarina Albizzia (Jurnal Masyarakat dan Desa, 2022)
One way to strengthen the agricultural sector is to form groups that care about the agricultural sector, one example is the forest farmer group. This research was conducted at the Sengon Mahogany Forest Farmers Group "JASEMA" in Terong Village, Dlingo District, Bantul Regency, Special Region of Yogyakarta. The community forest farmer group Jasema is one of the forums to empower its members. Jasema's strategy is to empower members with the existence of delayed logging cooperatives and participate in activities or programs, both comparative studies and trainings by Jasema management in the context of developing farmer group members so that they can add new knowledge and experience from various activities. participate. The type of research used is a qualitative approach. Qualitative research methods use qualitative observations, interviews, or document review. The strategies used in empowering farmer group members are 1. Increasing Adaptation to Changes in People's Mental Attitudes 2. Improving Operational Performance by Improving Policy Patterns to Improve the Quality of Human Resources (HR) and institutional strengthening. 3. Provide opportunities for weak people or communities to share power in the economic, political and socio-cultural fields